Smart City System Review: Challenges and Opportunities for Implementation in Urban Areas - Julinaldi, Julinaldi; Buang , Nursahar; Dody, Dody; Harahap, Muhammad Ade Kurnia (Journal of Renewable Engineering, 2025)
Rapid urbanization has pushed cities in Indonesia to face complex challenges related to infrastructure capacity, public services, and urban governance. Smart cities are seen as a strategic solution to build efficient, adaptive, and sustainable cities through the use of digital technologies such as the Internet of Things (IoT), artificial intelligence (AI), and big data. However, the implementation of smart cities in Indonesia still faces various obstacles, including digital infrastructure inequality, low human resource capacity, and weak institutional coordination. This study uses a qualitative descriptive approach and a SWOT analysis framework to identify the strengths, weaknesses, opportunities, and threats in the implementation of smart cities in urban areas in Indonesia. Data were obtained from policy literature studies, national and international agency reports, and smart city project documentation. The results of the study show that the success of smart cities is highly dependent on the synergy between infrastructure readiness, utilization of technological opportunities, and mitigation of socio-technological risks. Policies are needed that encourage cross-sector collaboration, citizen data protection, and strengthening digital literacy and local capacity. With a participatory approach and inclusive governance, smart cities can be an instrument for transforming cities that are not only technologically modern, but also socially just and sustainable in the long term.